Automated closed–loop FiO2 titration increases the percentage of time spent in optimal zones of oxygen saturation in pediatric patients–A randomized crossover clinical trial - Soydan, Ekin; Ceylan, Gokhan; Topal, Sevgi; Hepduman, Pinar; Atakul, Gulhan; Colak, Mustafa; Sandal, Ozlem; Sari, Ferhat; Karaarslan, Utku; Novotni, Dominik; Schultz, Marcus J.; Agin, Hasan (Frontiers in Medicine, 2022)
Introduction We aimed to compare automated ventilation with closed–loop control of the fraction of inspired oxygen (FiO2) to automated ventilation with manual titrations of the FiO2 with respect to time spent in predefined pulse oximetry (SpO2) zones in pediatric critically ill patients. Methods This was a randomized crossover clinical trial comparing Adaptive Support Ventilation (ASV) 1.1 with use of a closed–loop FiO2 system vs. ASV 1.1 with manual FiO2 titrations. The primary endpoint was the percentage of time spent in optimal SpO2 zones. Secondary endpoints included the percentage of time spent in acceptable, suboptimal and unacceptable SpO2 zones, and the total number of FiO2 changes per patient. Results We included 30 children with a median age of 21 (11–48) months; 12 (40%) children had pediatric ARDS. The percentage of time spent in optimal SpO2 zones increased with use of the closed–loop FiO2 controller vs. manual oxygen control [96.1 (93.7–98.6) vs. 78.4 (51.3–94.8); P < 0.001]. The percentage of time spent in acceptable, suboptimal and unacceptable zones decreased. Findings were similar with the use of closed-loop FiO2 controller compared to manual titration in patients with ARDS [95.9 (81.6–98.8) vs. 78 (49.5–94.8) %; P = 0.027]. The total number of closed-loop FiO2 changes per patient was 52 (11.8–67), vs. the number of manual changes 1 (0–2), (P < 0.001). Conclusion In this randomized crossover trial in pediatric critically ill patients under invasive ventilation with ASV, use of a closed–loop control of FiO2 titration increased the percentage of time spent within in optimal SpO2 zones, and increased the total number of FiO2 changes per patient. Clinical trial registration ClinicalTrials.gov, identifier: NCT04568642.